Separation of cholesterol from other steroids using molecularly imprinted polymer prepared by seeded suspension polymerization - Lee, Wen-Chien (Array, 2008)
Summary: Micron-sized particles of cholesterol-imprinted polymers were synthesized by seeded suspension polymerization in a mixture of 2-propanol and water using polystyrene microbeads as the seeds. Methacrylic acid was employed as the functional monomer to form complexes with template (cholesterol), along with ethylene glycol dimethacrylate as the crosslinker. After removal of template molecules, the columns (H = 15 cm, Di = 0.46 cm) packed with cholesterol-imprinted polymers were effective for the chromatographic separation of cholesterol from other steroids. When the sample of steroids was eluted isocratically at a flow-rate of Q = 0.5 mL min–1, using a mixture of acetonitrile and water (Y= 95:5) as the mobile phase, the retention times for estrone, -estradiol and cholesterol were respectively = 5.3, 12.3 and 17.2 min.The average retention times were = 5.3, 10.9 and 16.7 min respectively for estrone, progesterone and cholesterol in samples. The separation was based on the specific binding of cholesterol to recognition sites formed on the imprinted polymers.Aseparation factor of 1.6 for cholesterol and -estradiol was obtained.The chromatographic efficiency was dependent on the mobile phase composition.Reducing the water content in the non-polar mobile phase to zero could significantly enhance the separation. Compared with particles from bulk polymerization, the column packed with cholesterol-imprinted particles from seeded suspension polymerization had a higher chromatographic efficiency and the advantage of microanalysis